If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 8x + -1(6x + 7) = 0 Reorder the terms: 2x + 8x + -1(7 + 6x) = 0 2x + 8x + (7 * -1 + 6x * -1) = 0 2x + 8x + (-7 + -6x) = 0 Reorder the terms: -7 + 2x + 8x + -6x = 0 Combine like terms: 2x + 8x = 10x -7 + 10x + -6x = 0 Combine like terms: 10x + -6x = 4x -7 + 4x = 0 Solving -7 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 4x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 4x = 0 + 7 4x = 0 + 7 Combine like terms: 0 + 7 = 7 4x = 7 Divide each side by '4'. x = 1.75 Simplifying x = 1.75
| 4x+15-15+3-8x=13 | | 5s^2-17s=6 | | 3x+4(x-8)-x=0.6(10x+15) | | x^2+6=150 | | -.33x+30=-x+10 | | 4x+8-6=3x-12 | | P-1(4)=p+2(2) | | 7.43x+9=55.2049+3x | | 27=d-18 | | .83x-.16=4 | | x/4=10 | | 3w+2=w+7 | | 25x=-625 | | 2x^4=-250x | | 3(r+2)=-1(2r-4) | | 3*(-4)= | | x^2-5=157 | | x^2+x^2=12 | | (-3)*4= | | 16-8x-12=24+20 | | (-2)*(-8)= | | 9-4x+7x+15= | | 9x+17-7x+17=2 | | -5=-15 | | 7x+10=9x-4 | | (3x^2+5x-1)+(x^2-2x-7)=0 | | 6x-x-2x+8=7x | | 2(6x+2x)=2(x*x+12) | | -9.79(27x-65)=78.24(6x+34) | | 3x(x-5)-3x*3*3=-30 | | 5(x-6)-x=0 | | 2x*x+3x=3 |